Fundamental properties of unperturbed haematopoiesis from stem cells in vivo - Busch, Katrin; Klapproth, Kay; Barile, Melania; Floßdorf, Michael; Holland-Letz, Tim; Schlenner, Susan M.; Reth, Michael; Höfer, Thomas; Rodewald, Hans-Reimer (Nature, 2015)
Inducible genetic labelling of haematopoietic stem cells (HSCs) and linked mathematical modelling show that at least 30% of all HSCs are productive, and that adult haematopoiesis is largely sustained by ‘short-term’ downstream stem cells that operate near self-renewal in the steady state; HSC fate mapping provides a quantitative model for better understanding of HSC functions in health and disease.
Gesehen am 18.01.2021